Ada Twist, scientist. Exploring flight! - Beaty, Andrea; Griffith, Theanne; Stilwell, Steph (New York : Amulet Books, 2021)
"Discover everything there is to know about flight from Ada Twist, Scientst-from information about creatures that fly, to the history of aircrafts, to modern technology that allows us to soar through the air faster than ever!"--
"Netflix: a Netflix original series"--Front cover
"Includes two experiments to do at home!"--Back cover
Keywords: Flight -- Juvenile literature; Aeronautics -- Juvenile literature